Handling Disrupted Learning During COVID-19 Pandemic: Learners’ Experience in Nigeria - Folashade Afolabi (Journal of Educational Sciences, 2021)
Corona virus has affected not only human health but also educational sector. Schools were forced to suspend face-to-face learning while online learning was introduced.  How could learning be undisrupted during the lockdown period is the thrust of this paper. The paper examined the effectiveness of podcast (video recorded) lesson as a strategy in online teaching and to what extent the strategy met the needs of the learners during the challenging period of pandemic COVID-19. The study adopted mixed method research which consisted of the three main phases of design. Questionnaire which comprises of 19 items and divided into two sections was used for data collection while fifty (50) participants participated in the study. It was discovered that learners displayed positive perceptions towards the use of video recording lessons during pandemic period. Learners reported that online learning should be used to compliment face-to-face teaching even after the pandemic period.